Human capital in rural areas of the Chelyabinsk region - Abilova Ekaterina; Golovikhin Sergey (E3S Web of Conferences, 2021)
The significance and scientific novelty of the approach proposed in the article to the peculiarities of human capital formation in rural areas, acceptable for analyzing the current state of this phenomenon and constructing the optimal trajectory of its development, is substantiated, firstly, by taking into account the modern features of rural areas, including their multifunctionality; secondly, by positioning human capital not only as an individual, but also as a social phenomenon; thirdly, by integrating into the concept of such characteristics of human capital in rural areas as its relativity (network nature) and cumulativeness ( possibility of accumulation within territorial boundaries); fourthly, the identification of the human capital of rural areas as a complex adaptive system, spatially localized, associated with other systems, evolving under the influence of factors of micro-, meso-, macro-levels. The article discusses the concept of human capital in the context of rural areas and identifies their features. A logical scheme for the study of the peculiarities of the formation of human capital of agricultural business entities is proposed.